2008
DOI: 10.1007/s10719-008-9217-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycomics of bone marrow-derived mesenchymal stem cells can be used to evaluate their cellular differentiation stage

Abstract: Human mesenchymal stem cells (MSCs) are adult multipotent progenitor cells. They hold an enormous therapeutic potential, but at the moment there is little information on the properties of MSCs, including their surface structures. In the present study, we analyzed the mesenchymal stem cell glycome by using mass spectrometric profiling as well as a panel of glycan binding proteins. Structural verifications were obtained by nuclear magnetic resonance spectroscopy, mass spectrometric fragmentation, and glycosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 74 publications
12
69
0
Order By: Relevance
“…6). The most abundant biantennary N-glycans H5N4F1 (m/z 2244.1) and S1H5N4F1 (m/z 2605.3) were found to be core-fucosylated in undifferentiated MSCs and adipogenically differentiated MSCs since their fragmentation generated the two diagnostic One signal G1H5N4 at m/z 2461.2 was found to correspond to an N-glycan, which bears N-glycolylneuraminic acid and was also observed in a previous study [37] in MSCs, but this glycan was only found as a trace. This contaminant is most likely stemming from cell culture media that contain animal-derived components [38,39].…”
supporting
confidence: 81%
“…6). The most abundant biantennary N-glycans H5N4F1 (m/z 2244.1) and S1H5N4F1 (m/z 2605.3) were found to be core-fucosylated in undifferentiated MSCs and adipogenically differentiated MSCs since their fragmentation generated the two diagnostic One signal G1H5N4 at m/z 2461.2 was found to correspond to an N-glycan, which bears N-glycolylneuraminic acid and was also observed in a previous study [37] in MSCs, but this glycan was only found as a trace. This contaminant is most likely stemming from cell culture media that contain animal-derived components [38,39].…”
supporting
confidence: 81%
“…Other glycan markers have also been used to identify embryonic as wells as mesenchymal (adult) stem cells, such as high-mannose type N-glycans, linear poly-Nacetyllactosamine chains, alpha2-3-sialylation, and sialyl Lewis x epitopes [35][36][37]. Many of these are also cancerassociated antigens.…”
Section: Anti-hesc Mab Hesca-2 Binds To a Glycan 521mentioning
confidence: 99%
“…High mannose-type N-glycans are characteristic for undifferentiated bone-marrow derived MSCs from humans (73,75) and equines (76). Biantennary N-glycans are detected in adipose tissue-derived hMSCs (72).…”
Section: Mesenchymal Stem Cell Sialylated N-glycansmentioning
confidence: 99%
“…Biantennary N-glycans are detected in adipose tissue-derived hMSCs (72). Hybrid type N-glycans are found to be the less abundant type of N-glycosylation in undifferentiated and adipogenically differentiated hMSCs (73,75). In mice, an extraordinary branch is demonstrated by expression of GnT-V (the corresponding gene is Mgat5) in neural progenitor cells that have a self-renewal ability and multipotency (77).…”
Section: Mesenchymal Stem Cell Sialylated N-glycansmentioning
confidence: 99%